2015
DOI: 10.1364/oe.23.021204
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photo-response properties of a single ZnO microwire photodetector by coupling effect between localized Schottky barriers and piezoelectric potential

Abstract: The coupling effect between localized Schottky barriers (SBs) and piezoelectric potential that impact the photo-response properties of a single ZnO microwire (MW) photodetector (PD) is studied. Localized SBs is introduced by Au NPs decoration. The negatively charged Au NPs deplete more carriers near the ZnO surface, which raises the SB height and sharply reduces the recover time of the PD from 142.4 s to 0.7 s. Moreover, after applying the compressive strain, the band structure of ZnO MW changes and piezoelect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Our previous studies proved that the coupling between piezoelectric potential and numberd SBs (by Au NPs decoration) at the ZnO surface can much enhance the sensitivity of the piezoelectric devices. [23] For the Au NPs decorated piezoelectric transistor, the electrical transport properties of the device will be controlled more effectively by both the SB at the electrode contact and numberd SBs on the surface. The coupling among the characteristics of piezoelectricity, photoexcitation and semiconductor are enhanced because the numbered decorated Au NPs on the ZnO surface play the role of SBs, which supplies new and important control for field-effect-transistor (FET).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies proved that the coupling between piezoelectric potential and numberd SBs (by Au NPs decoration) at the ZnO surface can much enhance the sensitivity of the piezoelectric devices. [23] For the Au NPs decorated piezoelectric transistor, the electrical transport properties of the device will be controlled more effectively by both the SB at the electrode contact and numberd SBs on the surface. The coupling among the characteristics of piezoelectricity, photoexcitation and semiconductor are enhanced because the numbered decorated Au NPs on the ZnO surface play the role of SBs, which supplies new and important control for field-effect-transistor (FET).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, we proved that the localized SBs (by Au NPs decoration) at the ZnO surface is much enhanced the sensitivity of the piezoelectric devices. [23] Therefore, we believe that the numberd SBs can be functioned as traditional SB at the electrode to improve performance of the device, and using the coupling effect of piezoelectric potential and localized SBs to fabricate piezoelectric two-terminal transistors must be important to enhance the current on/off ratio of the devices.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the device is much smaller than the PB, shiing the 3D mechanical stage down for 1 cm equals to subjecting a tensile strain to the photodetector. 29,30 On the contrast, when shiing up the 3D stage, the photodetector receives a compressive strain. The deformation of photodetector 3 can be calculated from 3 ¼ d/2R, where d is the up/down moving distance of 3D stage, R is the bending curvature.…”
Section: The Performance Of Photodetector Under Uv Illuminationmentioning
confidence: 99%
“…Therefore, according to the piezo-phototronics theory, the performance of the UV photodetector can be monitored and strengthened by external strain. 29 Conventional UV photodetectors are usually manufactured on hard substrates like silicon, sapphire, ITO glass and all kinds of metal foil. With the revolution of science and technology, so portable electronic devices which remarkably facilitate people's life have shown large scientic potential and commercial perspective.…”
Section: Introductionmentioning
confidence: 99%
“…We estimated the time constants of rise stage are t 1 ¼ 6.27 s and t 2 ¼ 37.1 s, and their relative weight factors are 85 and 15%, respectively, which give an average rise time constant of t r ¼ 11.02 s; the estimated time constants of the decay stage are t 1 ¼ 0.28 s and t 2 ¼ 6.85 s, with relative weight of 67 and 33%, respectively, producing an average decay time constant t d of 2.43 s. It was found that the rise process of NW array PD (1.38 s) is much faster than that of single NW PD (11.02 s), while the resetting process of ZnO NW array PD (4.05 s) is also comparable with that of single NW device (2.43 s). [6,9,11,14,16,19,20,22,25,27,[33][34][35][36][37][38][39][40][41][42] Compared to low temperature synthesized ZnO nanorods reported in reference, [35,36] ZnO NW arrays grown by CVD at high temperature have better crystal quality, which contributes to the high performance of our devices. Table 1 compares the photoresponse of different ZnO NW-based UV PDs as reported previously.…”
Section: Photoresponse Behavior Of Zno Nw Uv Pdsmentioning
confidence: 99%